Ecological impacts of forest fire on composition and structure of tropical deciduous forests of central India. (December 2022) - Kumar, Gajendra; Kumar, Amit; Saikia, Purabi; Roy, P.S.; Khan, M.L.
Abstract: The present study highlights the forest fire hotspots based on daily forest fire occurrence during 2000–2020 and its subsequent long-term impacts on different vegetation types in Central India. The MODIS (MCD14DL) based study exhibited the recurrence of fire incidences in central and southern parts of forests and affected substantial parts of the deciduous broadleaf forest (31.56% of select forest type) and deciduous needleleaf forest (30.23%), shrubland (7.52%), mixed forest (9.80%), with the major forest fire peaks during March and April, while negligible fire incidences were observed in plantation and grassland. 72% of field transects (157 out of the 218 field transects) were observed under high anthropogenic influences as evidenced by a large number of cut stumps. Six species (out of 106 studies tree species) including Tectona grandis L.f. (occurrence in 98% of fire hotspots), Butea monosperma (Lam.) Taubert (66%), were observed to be highly fire-resistant, recorded in >50% of the forest fire hotspots regions. The major forest fires hotspots (p < 0.01) were observed in the Malwa plateau, Vindhyan ranges, and Satpura range during 2000–2020, as observed with high fire intensity. While the forest in the northern parts attributed a cold spot with reference to forest fires (p < 0.01). The study elucidated the high susceptibility of forest fire in deciduous forests in Central India and necessitated proper management of forest fires by encouraging fire-resistant species, and prioritization of regions under fire hazards through the adoption of preparedness and response strategies to minimize the forest fire impacts. Highlights: High incidences of forest fire recorded in the recent decades (2010–20: 55.91%) compared to 2000–2010 in Central India. Eastern, Western, and Central Madhya Pradesh state recorded as high forest fire hotspots. Fire affected deciduous broadleaf forest (82%), deciduous needleleaf forest (12%), shrubland (3%), & mixed forest (3%). High forest fire hotspots zones have the least tree density (228 ind. ha -1 ) and low dominance (8.76 m2 ha -1 ). T. grandis is the most fire-resistant tree species recorded in 98% fire hotspots in Central India.